Comportamento e organização dos cromossomos holocêntricos de heterópteros da região Sul do Brasil baseados em sequências repetitivas DNA, meiose e análise ultraestrutural - Bardella, Vanessa Bellini [UNESP] (2014)
The species of the suborder Heteroptera have holokinetic chromosomes, variation in chromosome number, inverted/achiasmatic meiosis in the sex chromosomes and accumulation of heterochromatin predominantly in chromosome ends. In the 30 species analyzed of the infraorders Pentatomomorpha and Cimicomorpha, variations in chromosome numbers and asymmetrical karyotypes were observed, especially in Reduviidae. The C-CMA3/DAPI banding also showed that there is variability in the distribution of heterochromatic bands between autosomes and alossomos, however, the predominant location of heterochromatin were in the chromosome terminals. The 18S rDNA sites were located mainly in the terminal regions, with a tendency to distributed among the autosomes in Pentatomomorpha, whereas in species Cimicomorpha there was greater variation between autosomes and alossomos. To a more detailed study of the origin and organization of families of repetitive DNA, Triatoma infestans was chosen as a model. This study showed the two sequences of AT-rich satellite DNA that predominate on the ends of chromosomes, are composed of short motifs with 79 bp and 33 bp, which were possibly originated from transposable elements known as giant Polintons. Cytogenetic comparisons of all samples studied in this work showed some trends, such as the predominance of the sexual system XY/XX, the preferred location of heterochromatin and 18S rDNA sites on the ends of chromosomes and the occurrence of holokinetic chromosomes. However, changes in the organization and asymmetry of karyotypes observed in each group show a relative dynamic in the genomes of these heteropteran